THE INDEPENDENCE YEARS OF THE REPUBLIC OF UZBEKISTAN ARE A PRIORITY ISSUE IN THE CURRENT DEVELOPMENT OF THE COUNTRY THROUGH THE SPHERE OF PHYSICAL CULTURE AND SPORTS - Yakubjonova Feruza Ismoilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the last four years, the adoption of a number of regulatory legal and regulatory regulations on this issue and the goals pursued by the Republic of Uzbekistan on the priority issue of the development of the country in every direction through the sphere of Physical Culture and sports during the years of independence has been deeply analyzed and revealed.